UPAYA MENINGKATKAN KEMAMPUAN MENGGAMBAR TEMATIS MELALUI TEKNIK MENGGARIS DAN MEWARNAI PADA KELOMPOK B TK GELATIK V MUARA JAWA TAHUN PELAJARAN 2020/2021 - Soraya, Rani; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2022)
The purpose of this study was to increase thematic drawing creativity through the Lines and Coloring Techniques for children in Group B of Gelatik V Muara Jawa Kindergarten using the Classroom Action Research method which was carried out in two cycles, each cycle covering the stages of planning, implementing, observing and reflecting. The results show the percentage of completeness of 12 children per cycle, namely 4 children (40%) completed and then given action in cycle I to 8 children (60%) which indicates that cycle I has increased slightly and cycle II 10 children (90%) have completed. So that the Thematic Drawing activities through the Line and Coloring Techniques can be increased in group B children at Gelatik V Muara Jawa Kindergarten for the 2020/2021 Academic Year.